Additive Manufacturing Technologies and Their Applications in Dentistry: A Systematic Literature Review - Dragana Oros; Marko Penčić; Marko Orošnjak; Slawomir Kedziora (Applied Sciences)
Additive manufacturing (AM) has emerged as a transformative technology in dentistry, enabling the production of patient-specific dental applications with reduced costs and fabrication times. Despite the growth of applications, a consolidated understanding of current 3D printing technologies, materials, and performance in dental settings remains fragmented. Here, we perform a Systematic Literature Review (SLR) using the PRISMA protocol, retrieving 19 closely related primary studies. The evidence is synthesized across three axes: application domain, AM technology, and critical quality parameters. Dental restorations, prosthetics, crowns, and implants are the most common applications, while fused deposition modeling, stereolithography, digital light processing, selective laser sintering, and laser-directed energy deposition are the most used technologies. AM materials include polymers, metals, and emerging biomaterials. Key quality determinants include dimensional accuracy, wear and corrosion resistance, and photosensitivity. Notably, biocompatibility and cytotoxicity remain underexplored yet critical factors for ensuring long-term clinical safety. The evidence also suggests a lack of in vivo studies, insufficient tribological and microbiological testing, including limited data degradation pathways of AM materials under oral conditions. Understanding that there are disconnects between the realization of the clinical and the economic benefits of 3D printing in dentistry, future research requires standardized testing frameworks and long-term biocompatibility validation.